Enabling Positive Change. Flow and Complexity in Daily Experience - Riva, Giuseppe (De Gruyter, 2015)
Personal psychological growth: Why are some people able to promote their own psychological growth (bold tag) and change toward complexity while others not? Is it possible to propose simple methodologies and instruments that would allow selection of positive experiences and hence develop a stronger and richer Self? This book describes the way to promote and foster positive psychological growth in everyday life, through simple instruments accessible to anyone. Positive psychological experience: The focal point of the approach is the concept of Flow of Consciousness, an experience of subjective psychological wellbeing that nourishes and complexifies the Self. The authors propose a wide overview of positive psychological experience (bold tag) considering individual characteristics and experiences, as well as the influence of context, culture and social relationship, and the effects of the immersion in a globalized world, like the increasing daily use of mediated communication technologies. In the various chapters, this conceptual frame is declined in different areas of research, either consolidated ones or new fields. Self-development tips: In a fresh and engaging style, the book transports the readers in a world of situations and opportunities through which they can identify themselves in a positive and stable self-development (bold tag) process. In the first two chapters the authors describe the impact of positive psychological experience in social and individual life. In the following chapters the reader discovers, accompanied by the exposition of concrete research results, the specific characteristics that may promote flow experience in several field of experience: the use of communication technology; the experience of social-networks; clinical settings and Psychotherapy; the psychological relation with environment, politics and social participation, school, sports, family business, mentor's influence, and the perception of quality of life in daytime. Everyday opportunities: This opportunity of interacting with different and various kinds of experiences, that may appear dispersive, will on the contrary bring the reader - who may choose this book both for professional or personal reasons - to understand the concept of personal psychological growth in the wider and more concrete perspective, and to comprehend which personal skills he may bring into play in order to improve his personality and his daily experience.